Propolis from Southwest of Parana produced by selected bees: Influence of seasonality and food supplementation on antioxidant activity and phenolic profile - CALEGARI,MATHEUS A. (2017)
ABSTRACT Propolis produced by selected bees Apis mellifera were collected from March to June of 2013 and in March of 2015 and analyzed in order to evaluate the influence of climate, colony of origin, and food supplementation of colonies on the content of total phenolic and flavonoid by chromatographic analysis and antioxidant activity by radical scavenging of 2,2-diphenyl-1-picrylhydrazyl hydrate (DPPH) and 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) and ferric reducing antioxidant power (FRAP) methods. The Principal Component Analysis (PCA) was carried out with propolis collected in 2013 and two clusters were formed. Propolis produced in the months of March and April showed a higher content of total phenolic compounds (TPC) and antioxidant capacity than those produced in May and June. The results of PCA obtained from samples collected in March of 2013 and 2015 showed two clusters, and propolis collected in 2015 were more bioactive and presented a higher content of TPC. The chromatographic analysis of extracts allowed the identification of phenolic acids p-coumaric, ferulic and caffeic with similar chemical profiles that could be closely related to the botanical origin of propolis. It can be concluded that the season and food supplementation of colonies influenced the chemical composition and the biological activity of samples analysed.